The safety and efficacy of the re-administration of gilteritinib in a patient with FLT3-mutated R/R AML with CNS relapse: a case report - Ji, Yueru; Wan, Zhuo; Yang, Jian; Hao, Miaowang; Liu, Li; Qin, Weiwei (Frontiers in Oncology, 2024)
FLT3-ITD is a type of poor prognostic factors in acute myeloid leukemia (AML) disease. Gilteritinib, the second-generation FLT3 tyrosine kinase inhibitor, improved the overall survival of patients with relapsed/refractory FLT3-mutated AML in the ADMIRAL phase III trial. However, few data are available on the efficacy and safety of gilteritinib-based therapy for FLT3-mutated AML with central nervous system (CNS) involvement. We performed gilteritinib to treat a patient with CNS relapsed AML after allogeneic hematopoietic stem cell transplantation. The positive antileukemic effect of gilteritinib may bring new hope for the treatment of FLT3-mutated AML with CNS relapse.